Las psicologías cognitivas y la psicología de la mente. Herencias, relaciones, tensiones y perspectivas - javevirtual (2022)
This article examines different conceptual approaches and historical perspectives on the study of Emotion. It considers the most recent hypotheses and basic findings including those from neuscience. According to lthese findings, the concept of the differentiated emotional process is emphasized even though it is connected to cognitive and motivational processes. Finally, it makes an approach to affective processes which have occasionally been treated indistinctly from emotional ones, hypothesizing some differential and relevant elements for its conceptualization.